Anmeldelser - Tvarnø Lind, Tore (Danish Yearbook of Musicology, 2008)
Review of: Jane Mink Rossen and Uri Sharvit: A Fusion of Traditions: Liturgical Music in the Copenhagen Synagogue. Odense: University Press of Southern Denmark, 2006